2012
DOI: 10.17221/6273-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Optimal inclusion level of butylated hydroxytoluene in semen extender improves the quality of post-thawed canine sperm

Abstract: ABSTRACT:The study was conducted to evaluate the potential cryoprotective effect of butylated hydroxytoluene (BHT) through post-thaw evaluation of canine semen and its optimal inclusion level. Ejaculated canine semen was extended in TRIS-glucose egg yolk extender containing various concentrations of BHT (0.5, 1.0, 1.5, 2.0, and 2.5mM). Semen was frozen at −196°C using 200 × 10 6 spermatozoa per 0.5 ml straws and post-thaw evaluation was carried out in terms of sperm motility, viability, plasma membrane integri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Concerning the influence of BHT on the functional competence of frozen-thawed dog spermatozoa, the current study indicated that inclusion of 1mM BHT in Tris based extenders caused a significant improvement in motility, viability, acrosomal integrity, plasma membrane integrity as well as sperm DNA integrity. These results are in agreement with a previous study of for Neagu et al (2010); Sahashi et al (2011) and Ziaullah et al (2012) who reported that BHT was found to improve significantly all postthawed canine semen quality parameters in terms of sperm motility, acrosomal integrity, hypo-osmotic swelling response, membrane integrity and viability at an inclusion level of 1mM in the extended semen. BHT has been used successfully for preservation of liquid semen in turkey tom (Donoghue and Donoghue, 1997) and to minimize cryoinjury in ram (Watson and Anderson, 1983), boar (Roca et al, 2004), cattle bull (Shoae and Zamiri, 2008), goat spermatozoa (Khalifa et al, 2008 andNaijian et al, 2013) and human spermatozoa (Merino et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Concerning the influence of BHT on the functional competence of frozen-thawed dog spermatozoa, the current study indicated that inclusion of 1mM BHT in Tris based extenders caused a significant improvement in motility, viability, acrosomal integrity, plasma membrane integrity as well as sperm DNA integrity. These results are in agreement with a previous study of for Neagu et al (2010); Sahashi et al (2011) and Ziaullah et al (2012) who reported that BHT was found to improve significantly all postthawed canine semen quality parameters in terms of sperm motility, acrosomal integrity, hypo-osmotic swelling response, membrane integrity and viability at an inclusion level of 1mM in the extended semen. BHT has been used successfully for preservation of liquid semen in turkey tom (Donoghue and Donoghue, 1997) and to minimize cryoinjury in ram (Watson and Anderson, 1983), boar (Roca et al, 2004), cattle bull (Shoae and Zamiri, 2008), goat spermatozoa (Khalifa et al, 2008 andNaijian et al, 2013) and human spermatozoa (Merino et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…BHT has been used successfully for minimizing cryoinjury in ram (Watson and Anderson, 1983), boar (Roca et al, 2004), cattle bull (Shoae and Zamiri, 2008), and goat spermatozoa (Khalifa et al, 2008). However, there are scanty reports (Neagu et al, 2010;Sahashi et al, 2011 andZiaullah et al, 2012) regarding its cryoprotective potentiality and optimal inclusion level in canine semen. Also, from the best membrane stabilizing substance is Equex STM paste when adding to semen extenders in 0.5% just before freezing (Schäfer-Somi et al, 2006) has shown beneficial effects on frozen-thawed dog semen with regard to post-thaw motility, thermoresistance, increased longevity and plasma membrane integrity (Rota et al, 1997;Peña and Linde-Forsberg 2000b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive ROS production during cryopreservation and after thawing not only degrade cellular membranes but may also damage DNA [4], further enhancing dysfunction [5]. To reduce oxidative stress, exogenous antioxidants are frequently added to cryopreservative solutions to sustain semen quality prior to AI [6]. Several studies have confirmed ROS scavenging capacity of various medicinal plant extracts to improve sperm motility and increase fertility rates [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The LPO process caused by ROS (H 2 O 2 ) is detrimental to sperm survivability. As a result of high contents of polyunsaturated fatty acids in the plasma membrane and lack of antioxidant enzymes, mammalian spermatozoa are susceptible to LPO induced damage and loss of sperm functions [27,28]. Increasing ROS generation under oxidative stress (OS) leads to increased sperm plasma membrane failure, damaged spermatozoa [29], reduced sperm cell cytoplasm [30], and finally a marked reduction in viability, the integrity of the sperm membrane, and fertilizing ability and increased damage to sperm DNA [31].…”
Section: Introductionmentioning
confidence: 99%